PENGARUH LATIHAN PLYOMATRIC (DECLINE HOP) TERHADAP POWER OTOT KAKI DAN TUNGKAI SISWA SSB RUMBAI PRATAMA U-17 PEKANBARU - Saputra, Rizki Nanda; Agust, Kristi; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Now the problem in this research is the lack of explosive power leg muscles and limbs, this is seen from the results of the leap into the air which is not a maximum or does not reach the criteria of learning in line with the specified minimum trainers agreement of SSB Rumbai Pratama u-17 Pekanbaru. The form of this research is the research experiments using the technique of the total sampling obtained samples consists of 18 people. The instrument used in this research is to use vertical jump power, which aims to measure the results of the leap into the air. After that is done pre test and exercise treatment for 16 meeting times to 18 students of SSB Rumbai Pratama u-17 Pekanbaru and then post test. The data in the process with the statistics, to test with test lilifors normalitas on equal is significant α 0,05. The proposed hypothesis is there any influence of the exercise plyomatric (decline hop)  to power the leg muscles and limbs on students SSB Rumbai Pratama u-17 Pekanbaru. Based on the analysis of the statistical data, there is any average of pre-test consists of 765,41 and the average of post-test consists of 804,66, then the data is normally distributed. Based on the analysis of the t tests produce a Ttest consists of  3,637 and Ttable consists of 1,740, its means Ttest > Ttable. Moreover, there is the influence of the exercise plyomatric (decline hop) to power the leg muscles and limbs on students SSB Rumbai Pratama u-17 Pekanbaru.